AB1314-HPR ECONOMIC EVALUATION OF THE DR. BART APP IN PEOPLE WITH KNEE AND/OR HIP OSTEOARTHRITIS. (2nd June 2020) - Pelle, T.; Bevers, K.; Van den Hoogen, F.; Van der Palen, J.; Van den Ende, C.
Abstract : Background: Self-management is of paramount importance in non-surgical treatment of knee and/or hip osteoarthritis (OA). Modern technologies offer the possibility to support self-management 24/7. We developed an e-self-management application (dr. Bart app) for people with knee and/or hip OA 1 . Objectives: To evaluate the (incremental) cost-utility and cost-effectiveness of the dr. Bart app compared to usual care in people with knee/hip OA, applying a health care perspective. Methods: This economic evaluation was conducted alongside a 6-month randomized controlled trial, in which 214 participants were offered to use the dr. Bart app for 6 months and 213 participants received care as usual. Health care costs were measured using self-reported questionnaires. Clinical outcome measures were quality-adjusted life years (QALYs) according to the EuroQol (EQ-5D-3L), the EuroQol rating scale (QALY-TRS), and the five subscales of KOOS/HOOS. Cost and effect differences were estimated using longitudinal linear mixed models and cost-effectiveness acceptability curves. Bootstrapping was used to estimate statistical uncertainty. Results: Mean age of participants was 62.1 (SD 7.3) years, with the majority being female (72%) (Table 1 ). The difference in health care costs was non-significantly in favour of the intervention group (€-31.12 (95% CI: -66; 3)). Table 2 shows estimated treatment effects over 6 months. We found small but positive effects on symptoms, pain and activities of daily living (ADL) in favour of the dr. Bart app group. For QALY and QALY-TRS, the probability of the dr. Bart app being cost-effective compared to usual care was 0.80 and 0.60 at a willingness to pay (WTP) of €10.000 and 0.72 and 0.44 at WTP €80.000, respectively. For symptoms, pain and ADL, the probability that dr. Bart app was cost-effective was > 82% and for activities and quality of life < 40%, regardless of WTPs. Conclusion: This economic evaluation, from a health care perspective, showed that costs were not significantly lower for the dr. Bart app group compared to usual care. Given the non-invasive character of the intervention and the moderate probability to be cost-effective for the majority of outcomes, the dr. Bart app has only the potential to serve as a trustworthy tool to provide education and goal setting regarding OA and its treatment options. References: [1]Pelle T, Bevers K, van der Palen J, van den Hoogen FHJ, van den Ende CHM. Development and evaluation of a tailored e-self-management intervention (dr. Bart app) for knee and/or hip osteoarthritis: study protocol. BMC Musculoskelet Disord [Internet]. 2019 Dec 31;20(1):398. Disclosure of Interests: None declared